Novel Strategy of Local Infiltration Anaesthesia for Cyst Removal - Xiao-Xiao Shi; Yuan-Jin Zhang; Xiao-Yan Yang; Ting-Ting Zhou; Ning Xu (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)